Extracurricular Partnerships as a Tool for Enhancing Graduate Employability - Lewis, David I (International Journal for Students as Partners, 2017)
The world of work is changing rapidly, with an increasing global demand for employees with higher-level skills. Employees need to have the right attitudes and aptitudes for work, possess work-relevant skills, and have relevant experience. Whilst universities are embedding employability into their curricula, partnerships outside of the taught curriculum provide additional, largely untapped, opportunities for students to develop these key skills and gain valuable work experience. Two extracurricular partnership opportunities were created for Bioscience undergraduates at the University of Leeds, UK: an educational research internships scheme, where students work in partnership with fellow students and academic staff on on-going educational projects, and Pop-Up Science, a unique, student-led public engagement volunteer scheme. Both schemes generate substantial benefits for all. They enhance student’s skills and employability, facilitate and enhance staff-student education practices and research, and engage the public with research in the Biosciences. Collectively, they demonstrate the extraordinary value and benefits accrued from developing extracurricular partnerships between students, staff, and the community.